The Analysis of Satisfaction of Public Service Accountability in the Office of Investment and Integrated Licensing Services (DPMPTSP) Jambi City, Jambi Province - Yusuf, Muhammad (Universitas Brawijaya, 2018)
Both good and clean government has raised an issue in the public administration study; one of them in the public service sector is accountability. Accountable become a demand from the public to public official which can be done by the government. Based on the Ombudsman Republic of Indonesia's supervision in eight government agencies of Jambi city, one of them is The Office of Investment and Integrated Licensing Service (DTMPTSP). The results of supervision indicated the service has not well; it is characterized by the absence of service standard; did not follow procedures and long chain service. One example, there were users completed documents for taking Building Permit (IMB), but it more than one month for taking licence. This study aims to describe the aspects of process accountability of service to the users. This study uses descriptive quantitative research, the researcher took the primary data includes survey, interview and observation, secondary data obtained from literature study and documentation. The results showed IMB service was not accountable, it is viewed by the disobedience of providers with applicable regulations, and public official is power oriented and less responsive in accommodating the public interest, less careful in serving the user and not available details of the cost of publishing licence.